2008
DOI: 10.1002/ejoc.200800324
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Hydrogen‐Bonding Pattern of a Glycosyl Donor: The Key to Understanding the Outcome of Sialylation

Abstract: Changes in the hydrogen‐bonding pattern in solutions of glycosyl donor induced by the addition of external amides/imides or by concentration changes influence the yield and stereoselectivity of sialylation. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…In the course of their investigation into their supramer concept, numerous such studies were reported by Kononov and coworkers for various sialidation reactions. 286290 A curious inverse dependence on acceptor concentration in certain sialidation reactions was reported by Xing and coworkers and attributed to a change on supramer constitution. 332 Yet further examples have been provided by Kononov who showed, inter alia, the influence of donor concentration on the stereochemical outcome of the reaction of an arabinofuranosyl bromide with dibutyl phosphate (Scheme 65).…”
Section: Use Of Cation Clocks To Determine Molecularitymentioning
confidence: 92%
“…In the course of their investigation into their supramer concept, numerous such studies were reported by Kononov and coworkers for various sialidation reactions. 286290 A curious inverse dependence on acceptor concentration in certain sialidation reactions was reported by Xing and coworkers and attributed to a change on supramer constitution. 332 Yet further examples have been provided by Kononov who showed, inter alia, the influence of donor concentration on the stereochemical outcome of the reaction of an arabinofuranosyl bromide with dibutyl phosphate (Scheme 65).…”
Section: Use Of Cation Clocks To Determine Molecularitymentioning
confidence: 92%
“…An attempt of developing of such an approach, which was reviewed, 111 has recently been made by Kononov et al 111,[165][166][167][168][169] They introduced a novel concept, a "supramer approach", 111 which emphasizes the importance of supramolecular aggregation in the reaction mixture leading to formation of supramers (short of supramolecular isomers) 110 of reagents, which are differently arranged supramolecular assemblies incorporating the solute (and solvent) molecules (see also the discussion below). According to this hypothesis, depending on the molecular structure and reaction conditions, molecules of reagents can form fundamentally different supramers, which can be distinguished by physical methods and differ in their chemical properties.…”
Section: Known Examples Of Inuence Of Supramolecular Aggregation In ...mentioning
confidence: 99%
“…For example, seemingly minor changes in reaction conditions, which signicantly modify the structure of supramers of the reacting solute, may lead to dramatic changes in the reaction outcome. 111,140,[165][166][167][168][169] Using the supramer approach, new variables, which can modulate stereochemical outcome of glycosylation reaction, have been discovered. The previously unrecognized factors include (1) concentrations of reagents, 167,169 (2) presence of other compounds in the reaction mixture (including "nonreacting" additives or reaction products), 165,[167][168][169] and (3) time 168 of reaction.…”
Section: Known Examples Of Inuence Of Supramolecular Aggregation In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…and a higher temperature (0 °C to room temperature), affording 203 in a lower yield of 52 %. The 1 H NMR spectra of 201 at various concentrations showed that its low reactivity was due to the formation of a cluster-like structure via intermolecular hydrogen bonding, as proposed by Kononov et al [108] N-phenyl trifluoroacetimidate 204 was quantitatively obtained from tetrasaccharide 202 and subsequently coupled with tetrasaccharyl Asn acceptor 205 in cyclopentyl methyl ether (CPME) to afford octasaccharide 206 in 91 % yield with good stereoselectivity (α/β = 3 : 1). After the removal of the benzylidene group from 206 by treatment with TFA, the resulting diol-type acceptor 207 was glycosylated with imidate donor 204 using TMSOTf in CPME at 0 °C.…”
Section: Synthesis Of Sialylated N-glycansmentioning
confidence: 76%